Pharmacokinetics of tolfenamic acid in red-eared slider turtles (Trachemys scripta elegans) - Corum, Orhan; Atik, Orkun; Durna Corum, Duygu; Er, Ayse; Uney, Kamil (Elsevier BV, 2019)
To determine the pharmacokinetics of tolfenamic acid (TA) after different routes of administration [intravenous (IV) and intramuscular (IM), 2 mg kg-1] and doses (IV, 2 and 4 mg kg-1) in red-eared slider turtles (Trachemys scripta elegans).Randomized experimental trial.Sixteen healthy red-eared slider turtles.Turtles were randomly assigned to two groups (n = 8 each). Group 1 received TA at a dose of 2 mg kg-1 IV and then IM, after a washout period of 30 days. Group 2 received 4 mg kg-1 TA IV. A noncompartmental analysis was used to calculate pharmacokinetic variables.No local and/or systemic adverse drug effects were observed in any turtle. Elimination half-life and mean residence time following IM administration at 2 mg kg-1 were significantly longer than those following IV administration. The bioavailability following IM administration was complete. The area under the plasma concentration-time curve, elimination half-life, mean residence time and total clearance were significantly different between the dose groups.The absence of adverse reactions in the turtles of the study of TA along with the favourable pharmacokinetic properties (the long half-life and the complete bioavailability) of TA administered at the single doses of 2 and 4 mg kg-1 suggest the possibility of its effective use in turtles. However, further studies are required to establish a multiple dosage regimen of TA and to evaluate the clinical efficacy of administering TA.
Keywords: Analgesics; Injections, Intravenous; Animals; ortho-Aminobenzoates; Injections, Intramuscular; Turtles; 3. Good health